BREAKEVEN WITH COUNTING METHOD FOR DETERMINING SECANT BEST CHOICE USING BASIC PROGRAMMING LANGUAGES - Sri Suhesti; Irfan. Skom. MM Irfan. Skom. MM (Jurnal Sistem Informasi, 2001)
Secant method is one method for finding the roots of an equation, one use of thismethod is to find where the breakeven breakeven calculation is used to determine thebest choice of two options that are available in the purchase of a particular type ofgoods, especially on credit.In selecting the goods, other than pay attention to quality, costs, profits will beobtained should also consider the period of consumption goods in order to bringprofits to pay the minimum.